Effect of Omega-3 Polyunsaturated Fatty Acids on Lipid Metabolism in Patients With Metabolic Syndrome and NAFLD - Šmíd, Václav; Dvořák, Karel; Šedivý, Petr; Kosek, Vít; Leníček, Martin; Dezortová, Monika; Hajšlová, Jana; Hájek, Milan; Vítek, Libor; Bechyňská, Kamila; Brůha, Radan (Hepatology communications, 2022)
Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease. n-3 polyunsaturated fatty acids (n-3-PUFAs) have been reported to ameliorate the progression of NAFLD in experimental studies; however, clinical trials have yielded contradictory results. The aim of our study was to assess the effects of n-3-PUFA administration on lipid metabolism and the progression of NAFLD in patients with metabolic syndrome. Sixty patients with metabolic syndrome and NAFLD were randomized in a double-blind placebo-controlled trial (3.6 g/day n-3-PUFA vs. placebo). During the 1-year follow-up, the patients underwent periodic clinical and laboratory examinations, liver stiffness measurements, magnetic resonance spectroscopy of the liver, and plasma lipidomic analyses. After 12 months of n-3-PUFA administration, a significant decrease in serum GGT activity was recorded compared with the placebo group (2.03 ± 2.8 vs. 1.43 ± 1.6; P < 0.05). Although no significant changes in anthropometric parameters were recorded, a significant correlation between the reduction of liver fat after 12 months of treatment-and weight reduction-was observed; furthermore, this effect was clearly potentiated by n-3-PUFA treatment (P < 0.005). In addition, n-3-PUFA treatment resulted in substantial changes in the plasma lipidome, with n-3-PUFA-enriched triacylglycerols and phospholipids being the most expressed lipid signatures. Conclusion: Twelve months of n-3-PUFA treatment of patients with NAFLD patients was associated with a significant decrease in GGT activity, the liver fat reduction in those who reduced their weight, and beneficial changes in the plasma lipid profile.
Keywords: Non-alcoholic Fatty Liver Disease; metabolismus lipidů; Fatty Acids, Omega-3; Humans; omega-3 mastné kyseliny; Metabolic Syndrome; lidé; Lipid Metabolism; metabolický syndrom; nealkoholová steatóza jater